(untitled) (Applied Biological Research, 2023)
This experiment was performed to detect the beneficial compounds present in seed oil of Sapindus marginatus. The oil from the seeds of S. marginatus (Sapindaceae family) was extracted by the Soxhlet extraction technique using petroleum ether as solvent at 60-800C. 22.18% oil was recovered from seeds sample. The chemical compositions of seeds were examined by using GC-MS technique. The GC-MS analysis showed that oil of S. marginatus contained more than 40 compounds in total peaks area, out of which we discussed here mainly six monounsaturated compounds according their retention time (RT) and percentage of peak area, molecular formula and molecular weight. GC-MS study revealed the presence of cis-vaccenic acid (C18:1), cis-13-octadecenoic acid (C18:1) and trans-13-octadecenoic acid (C18:1) at RT 22.18 and its peak area was 40.48% of the compounds present in high amounts; whereas cis-13-eicosenoic acid (C20:1), cis-11-eicosenoic acid (C20:1) and cis-10-nonadecenoic acid (C19:1) at RT 23.56 and peak area 7.74 normally present in low amounts in seed oil, these are prominent components in the seed oil.